SigCom LINCS: data and metadata search engine for a million gene expression signatures. Issue Volume 50:Issue W1(2022) (7th May 2022) - Evangelista, John Erol; Clarke, Daniel J B; Xie, Zhuorui; Lachmann, Alexander; Jeon, Minji; Chen, Kerwin; Jagodnik, Kathleen M; Jenkins, Sherry L; Kuleshov, Maxim V; Wojciechowicz, Megan L; Schürer, Stephan C; Medvedovic, Mario; et al.
Abstract: Millions of transcriptome samples were generated by the Library of Integrated Network-based Cellular Signatures (LINCS) program. When these data are processed into searchable signatures along with signatures extracted from Genotype-Tissue Expression (GTEx) and Gene Expression Omnibus (GEO), connections between drugs, genes, pathways and diseases can be illuminated. SigCom LINCS is a webserver that serves over a million gene expression signatures processed, analyzed, and visualized from LINCS, GTEx, and GEO. SigCom LINCS is built with Signature Commons, a cloud-agnostic skeleton Data Commons with a focus on serving searchable signatures. SigCom LINCS provides a rapid signature similarity search for mimickers and reversers given sets of up and down genes, a gene set, a single gene, or any search term. Additionally, users of SigCom LINCS can perform a metadata search to find and analyze subsets of signatures and find information about genes and drugs. SigCom LINCS is findable, accessible, interoperable, and reusable (FAIR) with metadata linked to standard ontologies and vocabularies. In addition, all the data and signatures within SigCom LINCS are available via a well-documented API. In summary, SigCom LINCS, available at https://maayanlab.cloud/sigcom-lincs, is a rich webserver resource for accelerating drug and target discovery in systems pharmacology. Graphical Abstract: